2015
DOI: 10.1007/s00359-015-1007-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and individual variation in gastropod central pattern generators

Abstract: Gastropod molluscs provide a unique opportunity to explore the neural basis of rhythmic behaviors because of the accessibility of their nervous systems and the number of species that have been examined. Detailed comparisons of the central pattern generators (CPGs) underlying rhythmic feeding and swimming behaviors highlight the presence and effects of variation in neural circuits both across and within species. The feeding motor pattern of the snail, Lymnaea, is stereotyped, whereas the feeding motor pattern i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…Gastropod feeding strategies are highly diverse and include rasping, grazing, sucking, suspension feeding, cutting, and hunting (Audesirk and Audesirk, ; Chase, ; Sakurai and Katz, ). Although there are differences in choice of prey and feeding habits of the species in this study, feeding in Melibe differs drastically in that it is highly specialized and unique in Gastropoda (Hurst, ; Watson and Trimarchi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastropod feeding strategies are highly diverse and include rasping, grazing, sucking, suspension feeding, cutting, and hunting (Audesirk and Audesirk, ; Chase, ; Sakurai and Katz, ). Although there are differences in choice of prey and feeding habits of the species in this study, feeding in Melibe differs drastically in that it is highly specialized and unique in Gastropoda (Hurst, ; Watson and Trimarchi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In many invertebrates, individual neurons can be identified from animal to animal within a species, allowing the neural circuits to be determined with cellular precision. Moreover, homologous neurons can be identified across species, permitting comparative analyses of CPG circuits and the rhythmic behaviours that they produce [4,5]. Thus CPGs provide extraordinary opportunities to study the evolution of behaviour and neural circuits.…”
Section: (A) Evolution Of Central Pattern Generatorsmentioning
confidence: 99%
“…Remarkably, we have also observed this atypical cleavage pattern in other anaspideans such as Stylocheilus striatus , Dolabrifera dolabrifera , Dolabella auricularia , and Aplysia dactylomela (unpublished data), suggesting that this pattern of cleavage may be conserved in the Anaspidea. Previous studies of the phylogenetic relationships of opisthobranchs using morphological and molecular data have suggested that the Anaspidea may be one of the most derived clades within the group (Wägele et al., ; Zapata et al., , ; Sakurai and Katz, ; Sevigny et al., ), so it is not surprising to see a most deviate pattern of cleavage in this order.…”
Section: Resultsmentioning
confidence: 96%